IMPROVING SPEAKING ABILITY ON PUBLIC SPEAKING CLASS BY USING ROLE-PLAYING TECHNIQUE OF ENGLISH EDUCATION DEPARTMENT STUDENTS - Nafisah Endahati (Universitas PGRI Yogyakarta, 2014)
This research aims to improve speaking ability on speaking for specific purposes class of class A1 students of English Education Department students, Faculty of Teacher Training and Education, PGRI University of Yogyakarta in the academic year of 2012/2013. The effort which was done is using role-playing as a technique in teaching and learning activities. This collaborative and participative action research consisted of three cycles, with plan, action, observation, and reflection in each cycle. The participants were the students of class A1 of English Education Department, Faculty of Teacher Training and Education, PGRI University of Yogyakarta. The data were collected by means of interviewing, recording technique, observing, and assessing. The qualitative data were analyzed through data reduction, data display and conclusion drawing, while the quantitative data was analyzed descriptively by counting the mean score and the score percentage of the result of the observation. The results of research show that using role-playing technique can improve students’ speaking ability on speaking for specific purposes class. It can be indicated by the improvement of the activity of speaking classroom English, the interaction between teacher and students, and the students and teacher’s attention. The improvement of speaking ability on classroom English is also supported by the improvement of students’ achievement in speaking performance to a mean score of 161,18 or 70,579% (cycle I), 176,31 or 76,956% (cycle II), and 198,16 or 85,797% (cycle III).